1991
DOI: 10.1111/j.1365-2036.1991.tb00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Quinidine single dose pharmacokinetics and pharmacodynamics are unaltered by omeprazole

Abstract: Omeprazole has been shown in previous studies to inhibit the hepatic metabolism of selected drugs. Quinidine is an antiarrhythmic and antimalarial agent with a low therapeutic index. We therefore examined the effect of 40 mg omeprazole daily for one week or placebo on the pharmacokinetics and pharmacodynamics of a single 400 mg dose of quinidine in 8 healthy volunteers in a double-blind crossover study.During placebo and omeprazole treatment, there was no significant difference in area under the time-plasma qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…The weak response in CYP3A4 mRNA by phenytoin in spite of known induction properties in vivo may be explained by the concentration used in vitro (10 mM), which is below the concentration (40Y80 mM) reported to cause induction in vivo (31). Omeprazole significantly induced CYP3A4 mRNA in the liver slices but is not reported to be an in vivo inducer (32). However, as for CYP1A induction, this can be explained by the supratherapeutic concentrations used in the study.…”
Section: Discussionmentioning
confidence: 67%
“…The weak response in CYP3A4 mRNA by phenytoin in spite of known induction properties in vivo may be explained by the concentration used in vitro (10 mM), which is below the concentration (40Y80 mM) reported to cause induction in vivo (31). Omeprazole significantly induced CYP3A4 mRNA in the liver slices but is not reported to be an in vivo inducer (32). However, as for CYP1A induction, this can be explained by the supratherapeutic concentrations used in the study.…”
Section: Discussionmentioning
confidence: 67%
“…(a–f) Predicted compared to observed plasma concentration‐time profiles of quinidine and 3‐hydroxyquinidine alone and after pretreatment with and/or concomitant administration of (a) carbamazepine, (b) fluvoxamine, (c) itraconazole, (d) R‐/S‐omeprazole, (e) rifampicin, and (f) R‐/S‐verapamil (low verapamil dose regimen). Population geometric means are shown as lines (solid: quinidine and 3‐hydroxyquinidinde alone, dashed: quinidine and 3‐hydroxyquinidinde during DDI), geometric standard deviations are shown as shaded areas and observed data are shown as dots (control) and squares (DDI) (±standard deviation, if reported) 26,32–36 . Quinidine doses indicate quinidine sulfate administration.…”
Section: Resultsmentioning
confidence: 99%
“…(a, b) For quinidine acting as a cytochrome P450 (CYP) 3A4 and P-glycoprotein (P-gp) victim, predicted drug−drug interaction (DDI) (a) area under the plasma concentration-time curve calculated between the first and last concentration measurement (AUC last ) and (b) maximum plasma concentration (C max ) ratios of quinidine and 3-hydroxyquinidine are plotted against their respective observed values after pretreatment with and/or concomitant administration of carbamazepine, cimetidine, fluvoxamine, itraconazole, R-/S-omeprazole, rifampicin, and R-/S-verapamil. 26,[32][33][34][35][36]43,44 (c, d) For quinidine acting as a CYP2D6 and P-gp perpetrator, predicted DD(G)I (c) AUC last and (d) C max ratios of dextromethorphan (DEX), dextrorphan-O-glucuronide (DXG), total dextrorphan (DTT), digoxin (DIG), metoprolol (MET), S-metoprolol (SME), and R-metoprolol (RME), mexiletine (MEX) and paroxetine (PAR) are plotted against their respective observed values after pretreatment with and/or concomitant administration of quinidine. 11,[37][38][39][40][41][42]45 The solid line represents the line of identity, whereas 1.25-fold and two-fold prediction limits are shown as dotted and dashed lines, respectively.…”
Section: Quinidinementioning
confidence: 99%
See 1 more Smart Citation
“…the study inclusion criteria were: a) healthy Caucasian volunteers, b) availability of information about the quinidine pharmacokinetics, ideally presented as a drug plasma concentration change in time, c) PD results presented as Qt/ QTc or ΔQT/ΔQTc (regardless of the correction type), thus comparable with the simulation outputs. Nine papers fulfilling such conditions were identified and used for the study (Belz et al, 1982;Ching et al, 1991;El-Eraky and Thomas, 2003;Fieldman et al, 1977;Kaukonen et al, 1997;laganiere et al, 1996;Min et al, 1996;Olatunde and Price Evans, 1982;Shin et al, 2007). Characteristics of the clinical studies derived from the identified papers are presented in Table 1.…”
Section: Datamentioning
confidence: 99%